2013
DOI: 10.1007/s10162-013-0382-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct Recordings from the Auditory Cortex in a Cochlear Implant User

Abstract: Electrical stimulation of the auditory nerve with a cochlear implant (CI) is the method of choice for treatment of severe-to-profound hearing loss. Understanding how the human auditory cortex responds to CI stimulation is important for advances in stimulation paradigms and rehabilitation strategies. In this study, auditory cortical responses to CI stimulation were recorded intracranially in a neurosurgical patient to examine directly the functional organization of the auditory cortex and compare the findings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 65 publications
3
31
0
Order By: Relevance
“…This finding may point to limited cortical adaptation to the implant signal, which confirms the reduced auditory discrimination ability observed in these individuals. Similarly, longer N1 latency and reduced ability to discriminate complex sounds has been previously observed in CI users (Timm et al, 2012), although some CI users may show similar N1 latencies compared with NH listeners (Jordan et al, 1997;Sandmann et al, 2009), in particular after long history of CI use (Nourski et al, 2013). It can be speculated that the N1 latency of our participants reduced beyond one year of CI use.…”
Section: Remarkable Changes In the Contralateral And Ipsilateral Audimentioning
confidence: 49%
“…This finding may point to limited cortical adaptation to the implant signal, which confirms the reduced auditory discrimination ability observed in these individuals. Similarly, longer N1 latency and reduced ability to discriminate complex sounds has been previously observed in CI users (Timm et al, 2012), although some CI users may show similar N1 latencies compared with NH listeners (Jordan et al, 1997;Sandmann et al, 2009), in particular after long history of CI use (Nourski et al, 2013). It can be speculated that the N1 latency of our participants reduced beyond one year of CI use.…”
Section: Remarkable Changes In the Contralateral And Ipsilateral Audimentioning
confidence: 49%
“…At high sound levels (Ն60 dB SPL), animals not treated with intrascalar injections of neomycin sulfate had prominent short latency responses Ͻ2.5 ms, likely reflecting the cochlear microphonic and auditory nerve compound action potentials and some degree of residual hearing. High thresholds for response were likely due to electrode insertion trauma and cochlear hair cell loss (Kennedy, 1987;Ni et al, 1992). In all animals, the implanted ear was occluded with ear impression material during neural recording sessions.…”
Section: Methodsmentioning
confidence: 99%
“…Several PET studies in CI users have shown dominant contralateral activation (Naito et al, 1995;Hirano et al, 1997), although one PET study in CI subjects early after implantation (Ͻ2 months) showed ipsilateral dominance of CI stimulation (Ito et al, 2004). There is evidence that in some users unilateral CI stimulation causes bilateral activation in auditory cortex (Herzog et al, 1991;Limb et al, 2010).…”
Section: Asymmetric Activation Of Auditory Cortex By Unilateral CI Stmentioning
confidence: 99%
See 2 more Smart Citations